2010
DOI: 10.2174/157339410791202565
|View full text |Cite
|
Sign up to set email alerts
|

From HPV Infection to Oncogenesis: A Brief Review of the Complex Immunobiological Events

Abstract: This article reviews the natural history of HPV infection covering key aspects of cell biology, virology and immunology. The oncogenic HPV lifecycle is characterised by infection in basal cells of anogenital epithelia with virus production dependent on epithelial differentiation and virions produced only in terminally differentiated cells. Natural control of an oncogenic type HPV infection depends on appropriate activation of innate immune mechanisms leading to stimulation of adaptive immunity in the form of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…This subnetwork might have an important role in prostate cancer. In fact, we found that this network demonstrates a very strong correlation among others; with the "Proliferation_positive regulation cell proliferation" which further validates that genes in this network may serve in the process of oncogenesis [ 45 , 46 ] (Additional File 4 , Figure S8). In addition, among GO molecular functions, "growth factor activity" was found to be significantly activated indicating, that this network may stimulate growth of cancer cells (Additional File 4 , Figure S9).…”
Section: Resultssupporting
confidence: 64%
“…This subnetwork might have an important role in prostate cancer. In fact, we found that this network demonstrates a very strong correlation among others; with the "Proliferation_positive regulation cell proliferation" which further validates that genes in this network may serve in the process of oncogenesis [ 45 , 46 ] (Additional File 4 , Figure S8). In addition, among GO molecular functions, "growth factor activity" was found to be significantly activated indicating, that this network may stimulate growth of cancer cells (Additional File 4 , Figure S9).…”
Section: Resultssupporting
confidence: 64%
“…The presence of these defined tumor-specific antigens forms an excellent basis for the development of strategies aiming to reinforce the immune response to combat cancer. It has long been known that the adaptive immune response, in particular T cells, confer protection against HPV-induced diseases [35,36]. However, it is likely that in some cases the natural immune response against these HPV proteins may have been compromised, e.g., in a chronic HPV infection or cancer by systemic and/or local immune regulatory or escape factors [37,38].…”
Section: Development Of Novel Treatmentsmentioning
confidence: 99%
“…The result is the release of E2F, which can bind and activate its DNA targets to promote cell cycle progression. With these efects, E6 and E7 are truly oncoproteins and are also responsible for cell transformation [36]. Expression of these oncogenes appears to be a critical step in the maintenance of the transformed stage and progression to invasive carcinoma.…”
Section: Vaccinesmentioning
confidence: 99%